ANALISIS KOMPETENSI PEDAGOGIK GURU DALAM MENINGKATKAN HASIL BELAJAR SOSIOLOGI DI KELAS X MAS AL-JIHAD PONTIANAK - Muthmainnah Muthmainnah; Supriadi Supriadi; Izhar Salim (ICoTE Proceedings, 2019)
The research was determine is "Teacher's Pedagogic Competence in Improving Learning Outcomes in Sociology Subjects in Class X of the Pontianak Al-Jihad MAS". The purpose of this study was to determine teacher planning in conducting sociology learning with the 2013 curriculum, to find out the implementation of teachers in conducting sociology learning with the 2013 curriculum, to describe evaluations conducted by teachers in sociology learning with the 2013 curriculum. The approach used was a qualitative approach with descriptive method . Data collection techniques used were interview techniques and documentation, with data collection tools in the form of interview guides and documentation. Based on the results of interviews and documentation that the researchers have done prove that the sociology learning plan carried out by the teacher is still not optimal because the device is still incomplete. Then the implementation of sociology learning has not been implemented well because it did not achieve the planned learning objectives, and the evaluation carried out in sociology learning was quite good because it had used the assessment criteria as planned.